2009
DOI: 10.1016/j.str.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Insight into Collagen Recognition by Discoidin Domain Receptor 2

Abstract: SummaryThe discoidin domain receptors, DDR1 and DDR2, are widely expressed receptor tyrosine kinases that are activated by triple-helical collagen. They control important aspects of cell behavior and are dysregulated in several human diseases. The major DDR2-binding site in collagens I–III is a GVMGFO motif (O is hydroxyproline) that also binds the matricellular protein SPARC. We have determined the crystal structure of the discoidin domain of human DDR2 bound to a triple-helical collagen peptide. The GVMGFO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(151 citation statements)
references
References 55 publications
4
145
0
2
Order By: Relevance
“…Sequence alignment demonstrated conservation of around 50% with DSDs in related proteins, CPX-2 and ACLP, and around 30% with DSDs from non-related proteins, with the highest identity shared with the collagen-binding DSDs from the DDRs. More detailed analysis revealed conservation of key residues involved in mediating the DDR-DSD -collagen interaction via the formation of an amphiphilic binding trench [16,17]. These residues are also conserved in CPX-2 and ACLP, with the latter reported to associate with collagen I in studies implicating ACLP in pulmonary fibrosis [18].…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 3 more Smart Citations
“…Sequence alignment demonstrated conservation of around 50% with DSDs in related proteins, CPX-2 and ACLP, and around 30% with DSDs from non-related proteins, with the highest identity shared with the collagen-binding DSDs from the DDRs. More detailed analysis revealed conservation of key residues involved in mediating the DDR-DSD -collagen interaction via the formation of an amphiphilic binding trench [16,17]. These residues are also conserved in CPX-2 and ACLP, with the latter reported to associate with collagen I in studies implicating ACLP in pulmonary fibrosis [18].…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…The molecular details of the DSD-collagen interaction have been elucidated through a combination of NMR studies [15], resolution of the crystal structure of the DDR2-DSD-collagen complex [16], and functional investigations exploring the collagen-binding site within the DDR1-DSD [17]. Together, these studies indicate that the four surface-exposed loops situated within the DSD combine to form an amphiphilic binding trench that binds to the GVMGFO motifs present in fibrillar collagens I-III [15,16,17]. Key residues that (Fig 2).…”
Section: In Silico Analysis Suggests the Dsd Of Cpx-1 May Bind Collagenmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been suggested that stimulating DDR1 with its ligand, collagen, causes aggregation [32][33][34]. Here, we label DDR1 with a SNAP-tag that has been stochastically linked to Alexa488 or Alexa546.…”
Section: Resultsmentioning
confidence: 99%